Predictors of maternal attachment among breastfeeding mothers in Jordan - Sawsan Abuhammad (Wiley, 2021)
Abstract Aim This study aims to investigate the difference in maternal attachment in different scenarios, that is among mothers who breastfed their infants and mothers who combined breastfeeding with other types of feeding and determine the predictors of maternal attachment in breastfeeding mothers. Design A survey was used to collect data from 222 mothers from Jordan University of Science and Technology in Jordan. Method Who used breastfeeding or mixed methods and had healthy infants aged from 3 to 12 months and who did not have postpartum complications. The survey was conducted in three healthcare centres in Irbid city, Jordan. Results Mothers only breastfeed their infants did not differ in their attachment compared with those who used mixed feeding methods (using breastfeeding with formula feeding). Many factors showed significant impact on maternal attachment, which includes the mother's education, if they have assistance in caring for their infant, marital relationship quality, the infant's gender and the planning for pregnancy.